2020
DOI: 10.1212/nxi.0000000000000885
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain

Abstract: ObjectiveTo explore the hypothesis that serum neurofilament light chain (sNfL) indicative of neuroaxonal damage may improve precise disease profiling with regard to cognition and neuropsychiatric symptoms, we analyzed potential associations of sNfL levels with cognitive test scores, fatigue, depression, and anxiety.MethodsPatients with relapsing-remitting and secondary progressive MS (SPMS) underwent an elaborated assessment including MRI, various cognitive tests, and patient-reported outcomes. We determined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…Overall, our findings suggest that miRNA dysregulation might be attributable to cognitive deficits rather than MS progression. In fact, no differences in the miRNA levels were observed in IB4-positive EVs from PMS compared to RRMS patients, and no direct correlation was found between miRNAs levels in CI patients and sNf-L serum concentration, a proposed predictor of poor clinical outcome in MS [64], whose role in tracking cognitive deficit in MS is still controversial [65][66][67][68]. However, higher miR150-5p levels directly correlated with sNf-L levels in the overall Italian cohort as well as in the Amsterdam MS Center cohort, implying a role of the miRNA in process.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, our findings suggest that miRNA dysregulation might be attributable to cognitive deficits rather than MS progression. In fact, no differences in the miRNA levels were observed in IB4-positive EVs from PMS compared to RRMS patients, and no direct correlation was found between miRNAs levels in CI patients and sNf-L serum concentration, a proposed predictor of poor clinical outcome in MS [64], whose role in tracking cognitive deficit in MS is still controversial [65][66][67][68]. However, higher miR150-5p levels directly correlated with sNf-L levels in the overall Italian cohort as well as in the Amsterdam MS Center cohort, implying a role of the miRNA in process.…”
Section: Discussionmentioning
confidence: 96%
“…The association of NfL and non-motor symptoms of MS (e.g., cognition, psychological disorders, and fatigue) has been examined. While some studies reported a significant inverse association between NFL levels and cognitive function ( Tortorella et al, 2015 ; Gaetani et al, 2019c ) and long-term fatigue ( Chitnis et al, 2018 ), others did not find any association ( Håkansson et al, 2019 ; Aktas et al, 2020 ). Cognitive symptoms and fatigue in MS are strongly associated with sleep quality, depression, DMT, disease duration and severity, and lesion localization ( Rocca et al, 2014 ; Berard et al, 2019 ; Palotai et al, 2019 ).…”
Section: Correlation Of Nfl Levels With Radiological and Clinical Findingsmentioning
confidence: 95%
“…Still, no specific soluble biomarkers are available for CI in MS, unlike other neurodegenerative diseases. Few studies focused on axonal damage and CI biomarkers in MS, mainly NfL, with conflicting results [16,45,46]; only one study described a correlation between CSF Aβ levels and CI [37]. In contrast, recently, Virgilio et al observed, in 62 patients, a correlation between CSF t-Tau and information processing speed and global cognition, whereas NfL and Aβ could not discriminate CI patients [36].…”
Section: Tau and Cognitive Impairmentmentioning
confidence: 99%